Self-concept in specific academic domain values and goals: A study of Comprehensive Multisectoral Lyceum students in Greece - Koumi, Ioanna (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF